أثر العوامل المتعلقة بتأهيل فريق المراجعة وإجراءات العمل الميداني على جودة تقارير المراجعة: (دراسة ميدانية ) - د . ناصر جمعة سعد الدين صالح (White Nile Journal for Studies and Research, 2026)
The study aimed at determining and measuring the impact of main factors affecting qualification of auditing teamwork that concerning field work and its effect on auditing report quality. Doing so, via dedicating the financial and academician point of views. The study revealed existence of effects from all exploited factors to auditing reports quality. The study recommended for more scientific and applied development to Professional Auditing Organizations concerning modern techniques of auditing in favor of auditing process improvement and its outputs. In addition to, merging point of views according to scientific knowledge and operational experiences. finally, to obligate head of departments to revise their works at Professional Auditing Organization